Hand injuries in young children from contact with vacuum cleaners. Issue 1 (1st January 2002) - Macgregor, D
Abstract : Objectives: To assess the incidence of injuries to young children sustained by contact with a domestic vacuum cleaner and to highlight the potential for significant injury. An increase in public awareness of these risks might result in a reduction in morbidity. Methods: Over a period of one year, all children attending with an injury sustained because of contact with a domestic vacuum cleaner had review of their case notes by the author. Results: Four children were identified as having sustained friction burns to a hand after contact with a vacuum cleaner. All required treatment and several review appointments before satisfactory resolution was achieved. Conclusions: Although the number of cases seen was small, the potential for significant injury must be emphasised and public awareness increased in an attempt to reduce morbidity.